Anthropometric characterization and muscle strength parameters in young female swimmers at national level: The relationship with performance in the 50m freestyle - Marinho, D. A.; Neiva, H. P.; Branquinho, L.; Ferraz, R. (Journal of Human Sport & Exercise, 2021)
The aim of this study was to characterize and compare the anthropometric characteristics and the explosive muscular strength of the upper and lower limbs in swimmers at the U-16 and U-15 level. In addition, the relationship between anthropometric characteristics, strength variables and performance in the 50 m freestyle was verified. All participants were analysed, regarding their anthropometric characteristics, their explosive muscle strength, and their performance in the 50 m freestyle swim. A total of 92 female swimmers (mean ± standard deviation: 14.08 ± 0.56 years old) participated in the study. The results showed that sub-16 swimmers had higher body mass values compared to sub-15 swimmers (p < .01). In addition, statistically significant differences were also found for upper limb strength indicators (p < .05). Finally, although no differences were found for performance in the 50 m freestyle test between the groups analysed, it was found that swimmers swam with different biomechanical patterns. It was concluded that although there were significant differences for the anthropometric indicators and explosive strength variables, the performance in the 50 m freestyle did not show any statistically significant variations, however the two groups of swimmers, swam with different biomechanical patterns.